Metal speciation in salt marsh sediments: Influence of halophyte vegetation in salt marshes with different morphology - Pedro, Silvia (2020)
Salt marshes provide environmental conditions that are known to affect metal speciation in sediments. The elevational gradient along the marsh and consequent differential flooding are some of the major factors influencing halophytic species distribution and coverage due to their differential tolerance to salinity and submersion. Different species, in turn, also have distinct influences on the sediment's metal speciation, and its metal accumulation abilities. The present work aimed to evaluate how different halophyte species in two different salt marshes could influence metal partitioning in the sediment at root depth and how that could differ from bare sediments. Metal speciation in sediments around the roots (rhizosediments) of Halimione portulacoides, Sarcocornia fruticosa and Spartina maritima was determined by sequentially extracting operationally defined fractions with solutions of increasing strength and acidity. Rosário salt marsh generally showed higher concentrations of all metals in the rhizosediments. Metal partitioning was primarily related to the type of metal, with the elements' chemistry overriding the environment's influence on fractionation schemes. The most mobile elements were Cd and Zn, with greater availability being found in non-vegetated sediments. Immobilization in rhizosediments was predominantly influenced by the presence of Fe and Mn oxides, as well as organic complexes. In the more mature of both salt marshes, the differences between vegetated and non-vegetated sediments were more evident regarding S. fruticosa, while in the younger system all halophytes presented significantly different metal partitioning when compared to that of mudflats.